2023
DOI: 10.1093/jalm/jfac093
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Status of US Adults Assessed as Part of the National Health and Nutrition Examination Survey Remained Unchanged between 2003–2006 and 2017–2018

Abstract: Background We compared serum vitamin C (VIC) status of the adult (≥20 y) US population in the National Health and Nutrition Examination Survey (NHANES) 2017–2018 with combined data from 2003–2004 and 2005–2006. Methods VIC was measured using HPLC with electrochemical detection. Mean data were stratified by age, sex, race/Hispanic origin, income, body mass index, dietary intake, supplement use, and smoking status. Prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Others have shown an inverse association between vitamin C status and ageing in men only [ 22 ] or even a small increase in vitamin C status in non-smoking older people [ 21 ], with the latter being attributed to higher supplemental intake in the older group. Large epidemiological studies have shown opposite trends to earlier studies, with an analysis of the US National Health and Nutrition Examination Surveys (NHANES 2003–2006 and 2017–2018) indicating higher vitamin C status and a lower or comparable prevalence of deficiency (<11 µmol/L) in people aged ≥60 [ 16 , 17 , 18 ]. The increased vitamin C status in older people appeared to be primarily related to higher vitamin C supplement intake [ 16 ].…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Others have shown an inverse association between vitamin C status and ageing in men only [ 22 ] or even a small increase in vitamin C status in non-smoking older people [ 21 ], with the latter being attributed to higher supplemental intake in the older group. Large epidemiological studies have shown opposite trends to earlier studies, with an analysis of the US National Health and Nutrition Examination Surveys (NHANES 2003–2006 and 2017–2018) indicating higher vitamin C status and a lower or comparable prevalence of deficiency (<11 µmol/L) in people aged ≥60 [ 16 , 17 , 18 ]. The increased vitamin C status in older people appeared to be primarily related to higher vitamin C supplement intake [ 16 ].…”
Section: Resultsmentioning
confidence: 95%
“…Large epidemiological studies have shown opposite trends to earlier studies, with an analysis of the US National Health and Nutrition Examination Surveys (NHANES 2003–2006 and 2017–2018) indicating higher vitamin C status and a lower or comparable prevalence of deficiency (<11 µmol/L) in people aged ≥60 [ 16 , 17 , 18 ]. The increased vitamin C status in older people appeared to be primarily related to higher vitamin C supplement intake [ 16 ]. Age categories <60 or <65 did not appear to be associated with differences in vitamin C status in the NHANES cohorts or the large French SU.VI.MAX study [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations